[LB.02.30] INSULIN RESISTANCE AS A DETERMINANT OF INSULIN-LIKE GROWTH FACTOR-1 CONCENTRATION CHANGES IN OBESE CAUCASIAN WOMEN TREATED WITH ORLISTAT, METFORMIN, OR DIET. (September 2017) - Pupek-Musialik, D.; Kujawska-Luczak, M.; Szulinska, M.; Skrypnik, D.; Musialik, K.; Swora-Cwynar, E.; Kregielska-Narozna, M.; Grzymislawski, M.; Bogdanski, P.
Abstract : Objective: The aim of the study was to compare the influence of weight-reducing interventions, including a calorie-restricted diet (LC), metformin (IM), or orlistat (IO) on serum insulin-like growth factor-1 (IGF-1) concentrations, with special respect to initial insulin resistance (IR) status. Design and method: 114 subjects were enrolled in this randomized open label trial. The participants were assigned to receive a low calorie diet (LC), an isocaloric diet and 500 mg metformin twice daily (IM) or isocaloric diet with 120 mg orlistat three times daily (IO). Before and after the intervention body mass index, lipid profile, alanine aminotransferase, aspartate aminotransferase, insulin, glucose, homeostatic model assessment (HOMA-IR), IGF-1, and visceral adiposity index were estimated. Results: The reductions in BMI, and body fat were significant and comparable in both insulin sensitive (IS) and IR groups. Within three intervention groups, when IS and IR groups were directly compared, a greater decrease in HOMA–IR was seen in the LC, a greater reduction in body weight in the IM, and a greater drop in body weight, body fat, and HOMA-IR in the IO HOMA-IR reduction was significantly greater in IR women. Women with IR showed a significant increase in IGF-1 concentration. We found significant positive correlations of deltaIGF-1 with: initial HOMA-IR and deltaHOMA-IR, initial triglyceride/high-density lipoprotein (TG/HDL) ratio and deltaTG/HDL ratio; initial VAI and deltaVAI. Conclusions: Only IR, premenopausal showed a significant rise in circulating IGF-1 serum concentrations despite the method of intervention. The increase in IGF-1 was parallel to the improvement of insulin resistance parameters.